(untitled) (African Journal of Law and Politics, 2025)
The earth has become a global village. It is a place where exchanges, movements of goods, services and people take place. Men live there in real interdependence. These different movements and exchanges constitute a whole that would be described as mobilities. The latter are, moreover, intrinsic to human nature. Besides this reality, there is another evidence: the law, regulator of life in society. As a result, mobility cannot be an isolated aspect of the legal framework. The relationship between law and mobility is therefore real. The purpose of this article is therefore to shed light on the actual influence of the law on mobility.